Motorization and its consequences: A mixed-methods study on the epidemiology, impact, and stakeholder perspectives of road traffic injuries among undergraduate two-wheeler riding students in Nepal - Nikita Bhattarai; Diksha Pokhrel; Pranil Man Singh Pradhan; Sunil Kumar Joshi (PLoS ONE, 2026)
Introduction Motorization has undeniably enhanced mobility and convenience, but it comes at a significant cost, as the increasing number of vehicles has led to a surge in road traffic injuries (RTIs) now a major global cause of disability and death. Over the past decade, the significant growth in two-wheelers has coincided with a rise in RTIs, creating an increasing concern for young individuals. This mixed-method study aims to explore epidemiology, assess their impact on undergraduate students, and gather key recommendations from stakeholders to improve road safety and reduce injury rates. Methodology The quantitative data collection was conducted among undergraduate students in the four colleges in Kathmandu district. The total number of participants in this study was 1217 students of 17–31 years of age. Furthermore, for the qualitative data collection, 5 Key informant interviews were conducted among various stakeholders. Results The prevalence of RTI in 2021–2022 was 23%. The most common injuries were bruises in the upper and lower limbs. It was seen that only 78% of the respondents had a driving license. The injuries led to academic loss and caused financial strain due to healthcare and vehicle repair expenses. 5 key recommendations to decrease the ever-increasing burden of RTI have emerged from the qualitative data analysis. Conclusion The study highlighted a high prevalence and impact of RTIs among undergraduate students along with 5 key recommendations that came forward from this study could be instrumental for road safety in Nepal.